Chicanos in America after the Mexican War - Vraukó, Tamás (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
In this paper a brief summary is provided of the situation of Mexican-Americans in the period from the mid-19th century to the end of the 20th century. Examples are taken mostly from works of literature and some from movies, in order to illustrate how Chicano intellectuals wish to uphold their cultural heritage in an Anglo society that was unfriendly towards them for a long time.
Keywords: Mexican-Americans; Hispanics; assimilation; Chicano